Population structure and genetic diversity of Brachiaria grass (Urochloa spp.) accessions from the Democratic Republic of Congo using DArTseq single nucleotide polymorphism markers - Mushagalusa, P.B.; Kimwemwe, P.K.; Katunga, D.M.; Mondo, J.M.; Cirezi, N.C.; Ayagirwe, R.B.; Bacigale, S.B.; Mutai, Collins; Muktar, Meki S.; Kimani, Wilson; Jones, Christopher S. (Wiley, 2025)
Brachiaria grass (Urochloa spp.) is one of the key forage grasses utilized in sub-Saharan Africa for improving livestock productivity, particularly in terms of milk production and feed sufficiency. Limited information on its genetic resources has hindered its breeding and conservation strategies. This study used a set of 199 accessions collected across the Democratic Republic of Congo, which were genotyped using the Diversity Arrays Technology Sequencing platform. A total of 5787 high-quality single nucleotide polymorphisms (SNPs) were used to evaluate genetic diversity and population structure. Markers were moderately informative in differentiating the accessions with average polymorphic information content and gene diversity of 0.29 and 0.08, respectively. Structure analysis showed seven sub-populations (K = 7) with admixture corresponding to the geographical sources of the accessions. Discriminant analysis of principal component (DAPC) and principal component analysis further classified the accessions into five and six clusters, respectively. Genetic clustering was consistent with the DAPC and showed five main clusters with variable membership coefficients. Most pairs of accessions (80.6%) had a Euclidean genetic distance above 0.25, suggesting that most of them were genetically diverse. Mantel tests revealed a positive correlation between geographic and genetic distance among populations (r  =  0.315, p  =  0.0001), demonstrating consistency with the isolation by distance model. Analysis of molecular variance revealed significant differences between sub-populations, 74.41%, and a high fixation index (Fst = 0.77) and low number of migrants per generation (Nm = 0.08), indicating high genetic differentiation and a low gene exchange among the sub-populations and suggesting the presence of different Brachiaria grass species in our collection. The results revealed significant genetic diversity in the Brachiaria grass collection, which could be explored in genetic improvement, marker-assisted breeding, and to enhance conservation management of this germplasm in the future.